COVID-19 pandemic: from sanitary crisis to historical emerging challenges - Mazeres Gaitero, Francisco Javier (2020)
Despite having been one of the first countries in the region to decree a state of health emergency and to take exceptional measures to prevent its spread, the most recent accounts of the evolution of the COVID-19 pandemic leave no doubt as to the magnitude of the tragedy on a national scale. Peru is now among the ten countries with the highest number of infections in absolute terms worldwide (second in Latin America after Brazil), in addition to leading the mortality rate in relative terms.